Effect of particle properties on forces on an immersed horizontal slat during start-up of a fluidized bed - Liu, Duiping; Zhang, Yongmin; Yuan, Yongsheng; Grace, John R. (Chemical engineering research & design, 2020)
Different gas-solids flow phenomenas have been observed during start-up of fluidized beds of different particulate materials. [Display omitted] •Forces on a horizontal slat during start-up of fluidized beds of different particulate materials were measured.•The immersed internals will be subject to more severe during start-up of fluidized beds of small particle size.•Different gas–solids flow phenomenas have been observed during start-up of fluidized beds of different particulate materials To study the effect of particle properties on forces acting on immersed internals during start-up of fluidized bed reactors, forces on a horizontal slat were measured in fluidized beds of four types of particulate materials (i.e. FCC catalyst particles and three silica sands of different sizes). The forces were measured by strain gauges adhered on the slat surface. Transient pressure signals were also measured synchronously by pressure transducers. The experimental results show that a high upward stress impulse appears in the measured stress signals during start-up of the fluidized beds of FCC particles and the two smaller-size silica sands. The peak stress impulse was several times larger than the magnitude of stress signals measured during steady state operation. However, in the fluidized bed of the coarsest silica sand, the peak stress impulse during start-up was much smaller, which is close to the magnitudes measured during steady state fluidization. For the three sizes of silica sands, the effective peak load densities on the slat decreased significantly with increasing particle size and were approximately proportional to the calculated fixed bed pressure drops of these beds based on Ergun equation. On the other hand, during start-up of the fluidized bed of FCC particles, particles near the bottom of the bed were difficult to mobilize and collapse, resulting in the bed expanding considerably and requiring more time to transform into a fluidized state. Potentially, internals immersed in the fluidized beds of small particles are easier to damage during the start-up stage. Effective measures (e.g. starting up the bed gradually with small increments of superficial gas velocity) must be implemented to reduce the possible risks for internals immersed in these fluidized beds.